2021
DOI: 10.3389/fphy.2021.746576
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Magnetic Flux Rope During Solar Eruption. I. Evolution of Toroidal Flux and Reconnection Flux

Abstract: Magnetic flux ropes (MFRs) constitute the core structure of coronal mass ejections (CMEs), but hot debates remain on whether the MFR forms before or during solar eruptions. Furthermore, how flare reconnection shapes the erupting MFR is still elusive in three dimensions. Here we studied a new MHD simulation of CME initiation by tether-cutting magnetic reconnection in a single magnetic arcade. The simulation follows the whole life, including the birth and subsequent evolution, of an MFR during eruption. In the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 58 publications
2
12
0
Order By: Relevance
“…These results support the hypothesis, especially concerning CME-MFRs, that the CME-MFR can be formed by magnetic reconnection during the corresponding flare process. And recent simulation results also indicate clearly that the reconnection flux contributes to the axial (toroidal) flux of the CME-MFR in the early stage (Jiang et al 2021a;Inoue et al 2018).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…These results support the hypothesis, especially concerning CME-MFRs, that the CME-MFR can be formed by magnetic reconnection during the corresponding flare process. And recent simulation results also indicate clearly that the reconnection flux contributes to the axial (toroidal) flux of the CME-MFR in the early stage (Jiang et al 2021a;Inoue et al 2018).…”
Section: Introductionmentioning
confidence: 84%
“…The CME-MFR containing significant amount of flux was likely formed during the eruption through dynamic evolution process in the solar atmosphere. Recently it was demonstrated by unique observational analysis and data-inspired numerical simulation (Xing et al 2020;Jiang et al 2021a) the "increase-to-decrease" behavior in the toroidal flux of the CME-MFR. However the applicability of such analysis to our events is beyond the scope of the current study.…”
Section: Estimation Of Magnetic Properties Of Mfrsmentioning
confidence: 99%
“…The peak in the product av seems to slightly lag behind the other peaks (see, e.g., Karpen et al 2012). A latest numerical simulation study by Jiang et al (2021a) showed better coincidence between the peak of the rate of change in kinetic energy and that in the reconnection rate. The overall temporal profiles generally coincide with each other among the corresponding changes in the reconnection rate, the CME acceleration, and the time-derivative of the soft-X ray flux.…”
Section: Parameters Source Region Amentioning
confidence: 89%
“…Additional ribbon brightenings after the main sequence may correspond to other types of reconnection not resulting in the deduction of axial flux. For example, the latest numerical simulation by Jiang et al (2021a) demonstrated the buildup of an MFR from magnetic reconnection with the axial flux of the MFR increasing initially in sync with the reconnection flux, then the axial flux started to decrease while the reconnection flux continued to grow. Apparently, not all reconnection flux over an extended period of time corresponds to the reduction in the axial flux of the MFR.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Ultimately, the guide field relative to the inflow magnetic field B in at the reconnection current sheet could be estimated incorporating advanced and high-resolution numerical models of flare reconnection (e.g. Jiang et al, 2021b;Dahlin et al, 2021).…”
Section: Measurements Of Shear and Inference Of Reconnection Guide Fieldmentioning
confidence: 99%